Simultaneous Cadmium(II)/Phenol Removal from Water by Mixed Micellar-Enhanced Ultrafiltration Using Brij 35/SDS - Zhao*, Baowei; Ran, Jingyuan; Zhong, Jinkui (Asian Journal of Chemistry, 2013)
Micellar-enhanced ultrafiltration (MEUF) using single sodium dodecyl sulfate (SDS) was extensively investigated in the wastewater treatment. The present study was based on micellar-enhanced ultrafiltration using mixed Brij 35/SDS to deal with imitated waste water containing cadmium(II) ions and phenol at low concentrations. The critical micelle concentration (CMC) of mixed Brij 35/SDS was detected by conductivity method. In micellar-enhanced ultrafiltration process, the feed mixed surfactant concentration, molar ratio of Brij35 to SDS and cadmium(II) and phenol concentrations in the permeate were investigated while the rejection efficiency and the permeate flux were evaluated. With the molar ratio of Brij 35 to SDS improved, the CMCs of mixed Brij 35/SDS were much less than that of pure SDS. The rejection efficiency of cadmium changed slightly while that of phenol increased with the molar ratio when the initial SDS concentrations were kept as 1, 2 and 3 mmol/L. Given 0.5 molar ratio of Brij 35 to SDS, the cadmium(II) and phenol rejection were both enhanced with the total surfactant concentration. It is concluded that the compositions of mixed anionic/nonionic surfactant should be considered in the micellar-enhanced ultrafiltration for combined polluted waste water according to the concentration level of inorganic and organic compounds.